Quetelet Index in Child Nutritional Diagnosis - Pajuelo, Jaime (1996)
A total of 1547 children of both sexes and between 6 and 9 years of age were studied. This sample is representative at national level and belongs to the data source of the Survey of Nutritional Status of the Peruvian Habitant ("Evaluacion del Estado Nutritional del Poblador Peruano" , ENPPE 1975) which was executed by the Institute of Nutrition . Anthropometric measures taken were weight and height. The children's nutritional status was analyzed using the Quetelet Index (w/h2), taking as break point level 5 and 15p for deficit and low weight, and 85 and 95p for overweight and excess, respectively. The standard reference used is the one described by Must et al. Weight and height average were also analyzed. There exists a higher prevalence of overweight (13.9%) than excess weight (4.4%). Low weight (3.6%) and deficit (0.8%) prevalence is lower. Children grow within the curve which corresponds to -1.5 an -2 SD. Weights are between -0.5 and -1 SD. As to the geoecologic domains, girls level of growth in the high jungle and north highland and boys growth in the north highland and low jungle are below -2 SD. In conclusion, the Quetelet Index gives a higher tendency to overweight and excess weighh that reflects the behaviour of weight and height by separate.